Romantic Relationship Characteristics and Adolescent Relationship Abuse in a Probability-Based Sample of Youth - Taylor, Bruce (Journal of interpersonal violence, 2021)
This study examines the longitudinal association between baseline adolescent romantic relationship characteristics and later adolescent relationship abuse (ARA). Data are from the first two waves of the National Survey on Teen Relationships and Intimate Violence (STRiV). Girls and boys ages 10 to 18 were recruited randomly from the children of adults participating in a larger national household probability sample panel. About three quarters of the sample identified as White, non-Hispanic. Controlling behavior by a romantic partner consistently predicted later ARA. Higher levels of controlling behavior in the relationship was associated with higher rates of sexual and/or physical ARA victimization and higher rates for similar acts of perpetration. More controlling behavior by the partner was also associated with higher rates of psychological ARA victimization (and higher rates for psychological ARA perpetration). Our results suggest that ARA prevention programs should have explicit discussions of the deleterious effects of controlling behavior with adolescents. Respondents reporting higher feelings of passionate love were also at higher risk of experiencing sexual and/or physical ARA victimization. This finding will need to be considered by clinicians and prevention specialist in their work with youth as a potential risk marker for ARA. Baseline reports of at least one form of ARA were predictive of 1-year follow-up rates of ARA in all of our models, underscoring a long line of research that past aggressive or violent behavior is one of the strongest predictors of current aggressive or violent behavior. We also observed that female respondents were twice as likely to be perpetrators of physical and/or sexual ARA as male respondents. Prevention messaging often is focused on girls as ARA victims and our results imply that messaging should also be directed toward girls as perpetrators.